2012
DOI: 10.1038/pr.2012.134
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptor antagonist attenuates oxidative stress in a neonatal sepsis piglet model

Abstract: Background: Oxidative stress (oxidant-antioxidant imbalance) plays an important role in the pathophysiology of neonatal sepsis. This study evaluated whether an antisense peptide endothelin receptor antagonist, eTR-P1/fl, could attenuate oxidative stress in a neonatal sepsis model. Methods: a total of 18 3-d-old piglets were anesthetized and mechanically ventilated. six piglets received cecal ligation and perforation (cLP group) for induction of sepsis. six piglets also received continuous infusion (0.05 mg/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…The infusion of endothelin receptor antagonist ETR-P1/fl was proved effective in reducing serum nitrite and nitrate, TNF-alpha, and HMBG-1 in a piglet model of neonatal sepsis and also in reducing pulmonary hypertension and increasing mean arterial pressure and survival time [ 123 ] ( Table 3 ). In accordance with this study, in the same animal model, treatment with ETR-P1/fl reduced TH, OSI (calculated as total hydroperoxide/biological antioxidant potentials), and IL-6 at 3 and 6 hours after CLP, indicating attenuation of prooxidant and proinflammatory insult [ 124 ]. At present, endothelin receptor antagonists have never been investigated in clinical settings in the newborn.…”
Section: Antioxidant Strategies In Neonatal Sepsissupporting
confidence: 66%
See 1 more Smart Citation
“…The infusion of endothelin receptor antagonist ETR-P1/fl was proved effective in reducing serum nitrite and nitrate, TNF-alpha, and HMBG-1 in a piglet model of neonatal sepsis and also in reducing pulmonary hypertension and increasing mean arterial pressure and survival time [ 123 ] ( Table 3 ). In accordance with this study, in the same animal model, treatment with ETR-P1/fl reduced TH, OSI (calculated as total hydroperoxide/biological antioxidant potentials), and IL-6 at 3 and 6 hours after CLP, indicating attenuation of prooxidant and proinflammatory insult [ 124 ]. At present, endothelin receptor antagonists have never been investigated in clinical settings in the newborn.…”
Section: Antioxidant Strategies In Neonatal Sepsissupporting
confidence: 66%
“…Most of the studies assessing antioxidant enzyme activity in neonatal sepsis were based on serum measurements that could be influenced by hemolysis processes and in fact provided partially different evidences in comparison to observations based on erythrocyte level measurements [ 68 ]. Moreover, data obtained from animal studies on oxidative stress markers or antioxidant treatments in neonatal sepsis may not strictly reflect the clinical conditions of septic newborns, as in experimental settings, the animal models are challenged with high levels of LPS or bacteria, which is often not the case in clinical practice [ 52 , 53 , 117 , 118 , 123 , 124 ]. As regard to clinical observations, not all of the studies reported rigorous inclusion criteria, defining whether both EOS and LOS or only one of the two categories is included; therefore, conclusions derived from these studies could be misleading as redox pathophysiology of EOS and LOS could be partially different.…”
Section: Discussionmentioning
confidence: 99%
“…Naringenin inhibited O 2 − -induced prepro-ET-1 mRNA expression. Furthermore, activation of the ET receptors promotes oxidative stress and reduces the free radical scavenging ability [ 58 ]. Therefore, it is likely that ET-1 also contributes to the regulation of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental data indicate that ET-1 is involved in the pathogenesis of sepsis [8, 47, 50], viral and bacterial pneumonia [9, 10], Rickettsia conorii infections [11], Chagas disease [13, 48], and severe malaria [15, 17, 51, 52]. ET-1 is associated with vasospasms, vascular damage, blood brain barrier (BBB) permeability, cardiovascular remodeling, and inflammation [19, 20, 46, 53, 54].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of ET-1 are found in alveolar macrophages, leukocytes [5] and fibroblasts [6]. Clinical and experimental data indicate that ET-1 is involved in the pathogenesis of sepsis [7, 8], viral and bacterial pneumonia [9, 10], Rickettsia conorii infections [11], Chagas disease [12, 13], and severe malaria [14-17]. In this minireview, we will discuss the role of endothelin in the pathogenesis of infectious processes.…”
mentioning
confidence: 99%